Oeroeg - Launspach, Erik; Schwab, Martin; Krabbe, Jeroen; Faber, Peter; Hylkema, Hans; Van de Velde; Voorthuysen, Paul; Keuris, Tristan; Van den Ende, Walther; Louw, Ot; Haasse, Hella S. ([Netherland?] : PV Pictures, 1993)
Johan Ten Berghe joins the Dutch army when the Durtch East Indies unilaterally declare independence as Indonesia. He initiates his naive driver Twan in life in the East, having grown up there as son of colonial official Hendrik, now missing. Their adventures intertwine with Johan's childhood memories, especially concerning his native best friend, Oeroeg, who joined the rebellion, as well as their nanny and later de facto stepmother. Conflicting loyalties become tangible in extreme situations.
"Naar het boek van Hella S. Haasse"--Container insert.
Director, Hans Hylkema ; screenwriter, Jean van de Velde ; producer, Paul Voorthuysen ; music director, Tristan Keuris ; cinematography, Walther van den Ende ; editor, Ot Louw.
Erik Launspach, Martin Schwab, Jeroen Krabbe, Peter Faber.
In Dutch, with some dialogues in Indonesian.
Keywords: Feature films